Ginseng Compatibility Environment Attenuates Toxicity and Keeps Efficacy in Cor Pulmonale Treated by Fuzi Beimu Incompatibility Through the Coordinated Crosstalk of PKA and Epac Signaling Pathways - Huang, Yingying; Li, Lili; Li, Xiaojin; Fan, Simiao; Zhuang, Pengwei; Zhang, Yanjun (Frontiers in Pharmacology, 2018)
Cor pulmonale is characterized by severe right ventricular dysfunction caused by lung disease, particularly chronic obstructive pulmonary disease, which can lead to pulmonary hypertension. Our previous study has demonstrated that Fuzi and Beimu compatibility (FBC), a traditional TCM compatibility taboo, improves lung function in early-stage of pulmonary hypertension through the synergistic action of β-ARs signals. However, FBC increases cardiotoxicity with prolonged treatment and disease progression. Considering that the compatibility environment influences the exertion of the medicine, we selected ginseng for coordinating the compatibility environment to improve the security and extend the therapeutic time window of FBC. Monocrotaline-induced cor pulmonale rats were treated with FBC, ginseng, or ginseng combined with FBC (G/FBC). Then, the pulmonary and cardiac functions of the rats were examined to evaluate the toxicity and efficacy of the treatments. The crosstalk between PKA and Epac pathways was also studied. Results showed that G/FBC ameliorated lung function similar to or even better than FBC treatment did. Furthermore, G/FBC treatment attenuated FBC-induced cardiotoxicity, which significantly restored cardiac dysfunction and clearly decreased myocardial enzymes and apoptosis. The βAR-Gs-PKA/CaMKII pathway was inhibited and the Epac1/ERK1/2 axis was activated in G/FBC group. These findings indicate that ginseng compatibility environment could improve pulmonary function and attenuate cardiotoxicity in cor pulmonale via the coordinated crosstalk of PKA and Epac pathways, implying that ginseng could be used to prevent detrimental cardiotoxicity in cor pulmonale treatment.